The 1838 Mormon War in Missouri - LeSueur, Stephen C. (Columbia, Mo. : University of Missouri Press, 1990)
While much has been written on the Mormon War in past decades, Stephen C. LeSueur takes a fresh and much-needed new look. Writing in clear, straightforward prose, LeSueur has produced a thorough and thoughtful study that makes several important contribution ...
Includes bibliographical references (p. 268-277) and index.
Description based on print version record.
Keywords: Mormons -- Missouri -- History -- 19th century; Missouri -- History; HISTORY -- State & Local; HISTORY -- State & Local -- General; Electronic books